2000
DOI: 10.1159/000029941
|View full text |Cite
|
Sign up to set email alerts
|

The Stripping Technique: In vitro Absorption and Penetration of Five UV Filters on Excised Fresh Human Skin

Abstract: This article gives the results of a study whose aim was to compare the compartmental distribution and absorption of 5 UV filters, in vitro, by fresh human skin, after exposure times of 30 min and 16 h. These UV filters from BASF (octyl methoxycinnamate, benzophenone 4, benzophenone 3, octyl triazone and octocrylene) were incorporated separately in a simple oil-in-water emulsion. The composition of the emulsions was designed in order to obtain a sun protection factor of 5. Therefore the UV filters were introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 7 publications
1
45
0
1
Order By: Relevance
“…The results of a recent study suggested that the inorganic sunscreen Tinosorb M ® concentrates in the uppermost part of the stratum corneum [37]. UV filters possessing low lipophilicity such as padimate-O (logP o/w = 3.86) [15] and oxybenzone (logP o/w = 3.58) [7,8,16,17] had a higher skin permeability. The percutaneous absorption of oxybenzone in human volunteers was well correlated with in vitro results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a recent study suggested that the inorganic sunscreen Tinosorb M ® concentrates in the uppermost part of the stratum corneum [37]. UV filters possessing low lipophilicity such as padimate-O (logP o/w = 3.86) [15] and oxybenzone (logP o/w = 3.58) [7,8,16,17] had a higher skin permeability. The percutaneous absorption of oxybenzone in human volunteers was well correlated with in vitro results.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in vitro methodologies are now widely used for the assessment of percutaneous absorption of cosmetic ingredients [10,11]. The usefulness and relevance of in vitro studies for evaluating the in vivo percutaneous absorption of sunscreens have been demonstrated over the last few years [8,9,[12][13][14][15][16][17][18]. However, the ultimate goal is the quantification of the systemic exposure and the extrapolation of in vitro results to the actual human systemic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The only reports found in the literature on the percutaneous penetration of EHT were based on in vitro investigations using rat skin [19], porcine ear skin [10], and excised human skin [6]. These studies showed, in accordance with the data reported here, that diffusion of EHT into the stratum corneum was lower than that of OMC [6, 19] and other UV filters (e.g., diethylamino hydroxybenzoyl hexyl benzoate, bis-ethylhexyloxyphenol methoxyphenyl triazine, and octocrylene) [6, 10]. However, the percentage of the applied EHT dose having permeated had not been measured.…”
Section: Resultsmentioning
confidence: 99%
“…However, at variance with other UV filters, there are only scarce data available regarding the skin permeability of EHT [3, 10]. Moreover, the few published studies reported in the literature were performed in vitro on excised animal or human skin [3, 6, 9, 10, 19] mounted in Franz-type diffusion cells and on a human skin culture model [19]; in vivo studies in humans are lacking. This is a disadvantage, since in vitro experiments, even when they mimic realistic exposure conditions, cannot provide conclusive information but only some useful indication for the prediction of percutaneous absorption [3, 20], which is why experimentation on in vivo human skin remains the most reliable way to study skin permeation [3, 20].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 For the stratum corneum, the evidence of a reservoir effect was first shown by Vickers in 1963 for topical corticosteroids. 20 The finding was then confirmed for a number of other chemicals (e.g., nicotine, 22 caffeine, 23 cationic b-blocking drugs, 24 sunscreen agents, 25 and chlorpyrifos 26 ). Several parameters determine the duration of the reservoir effect, such as the nature of the permeant, the vehicle used, skin temperature, and the relative humidity to which the skin is exposed.…”
mentioning
confidence: 92%